Optimising effective parameters to improve performance quality in lateral flow immunoassay for detection of PBP2a in methicillin-resistant Staphylococcus aureus (MRSA). Issue 1 (1st January 2020) - Amini, M.; Pourmand, M. R.; Faridi-Majidi, R.; Heiat, M.; Mohammad Nezhady, M. A.; Safari, M.; Noorbakhsh, F.; Baharifar, H.
Abstract: Lateral flow immunoassay (LFIA) is the most widely used platform of the point-of-care (POC) detection. Since the most important factor in deciding the results of this technique is the visual quality of the test, it should be at its optimum. To address this issue, the present study examines optimising critical parameters to improve the quality of LFIA performance. In this regard the penicillin-binding protein 2a (PBP2a) in methicillin-resistant staphylococcus aureus (MRSA) was selected as a bacterial model. The targeted parameters included a) size of gold nanoparticles (AuNP), b) antibody conjugation conditions with AuNP, c) antibody concentrations in the capturing zones, d) the effects of blocking substances and different chemical buffers for pre-treatment of the strips. Visual quality of different manufactured strips revealed that the diameter of 14 ± 2, PH = 9.5 was the optimum for improvement of MRSA detection quality. The optimum concentration of labelling antibody in conjugate pad and concentration of the capturing antibody in the test band were 40 µg/ml and 1.1 µg/μl in PBS buffer (pH 7.4) respectively. In conclusion by finding the critical factors affecting the detection limit of lateral flow and optimising them, the visual quality of LFIA results can be increased.